A novel method for fabric color transfer. Issue 3 (10th March 2014) - Zheng, Dejun
Abstract Fabric color design is a complex process in textiles and clothing industry. A new method for fabric color selection and transferring is proposed in this study. An automatic way to select the colors from the natural images is developed for fabric color design. Based on these colors, a fabric image is then used for color transferring. The fabric image is processed by a bias field estimation operation, and the membership function of the color deviations of the image has been obtained. According to the selected colors and the color membership function, the fabric image colors can be changed and transferred to a new image that preserves the similar texture appearance but with significantly different color effects. The experimental results confirm the effectiveness of the proposed method. © 2014 Wiley Periodicals, Inc. Col Res Appl, 40, 304–310, 2015